Genetic Diversity and Population Structure of Cowpea (Vigna unguiculata (L.) Walp.) Landraces from Portugal and Mozambique - Joana Bagoin Guimarães; Cátia Nunes; Graça Pereira; Ana Gomes; Nascimento Nhantumbo; Paula Cabrita; José Matos; Fernanda Simões; Maria Manuela Veloso (Plants, 2023)
Cowpea (Vigna unguiculata (L.) Walp.) is currently a legume crop of minor importance in Europe but a highly relevant staple crop in Africa and the second most cultivated legume in Mozambique. In Portugal and Mozambique, cowpea’s phenotypic and genetic variation has been maintained locally by farmers in some areas. We used the molecular markers SSR, SilicoDArT and SNP to analyze the genetic diversity and population structure of 97 cowpea accessions, mainly from Portugal (Southern Europe) and Mozambique (Southern Africa). As far as we know, this is the first time that the genetic variation and the relationship between cowpea landraces collected in Portugal with those originated in Mozambique is reported. Despite the shared historical past, the Portuguese landraces did not share a common genetic background with those from Mozambique, and two different gene pools were revealed. Knowledge of the genetic structure of cowpea landraces offers an opportunity for individual selection within landraces adapted to particular eco-physiological conditions and suggests the existence of a valuable gene pool for exploitation in future Portugal-PALOP (Portuguese-speaking African countries) cowpea breeding programs.